Solid and Gaseous Methane in IRAS 23385+6053 as Seen with Open JWST Data - Ruslan Nakibov; Varvara Karteyeva; Igor Petrashkevich; Maksim Ozhiganov; Mikhail Medvedev; Anton Vasyunin (The Astrophysical Journal Letters)
We present a new description of the 7.7 μ m region towards the high-mass star-forming region IRAS 23385+6053 taken from the open James Webb Space Telescope Mid-Infrared Instrument Medium Resolution Spectrometer data. This area is commonly attributed to the ν _4 deformation mode of methane ice. For the first time, gaseous and solid methane were analyzed simultaneously in IRAS 23385+6053. The band at 7.58–7.8 μ m (1320–1280 cm ^−1 ) is interpreted as a wide solid absorption methane feature overlapped by the sharp features of the methane emission. We report the detection of gaseous methane and estimate its emitting area radius R , temperature T , and column density N as R = 2940 au, $T=10{3}_{-11}^{+13}$ K, and $N=0.7{8}_{+6.18}^{-0.64}× 1{0}^{17}$ cm ^−2 , correspondingly. The ice content was analyzed with the laboratory spectra data set of methane in different molecular environments obtained on the Ice Spectroscopy Experimental Aggregate. We were able to describe the wide feature of solid methane with the following laboratory spectra: CH _4 : CO _2 = 1 : 5 (at $27.{4}_{-10.8}^{+6.0}$ K) and CH _4 : H _2 O = 1 : 10 (at $8.{4}_{-1.7}^{+16.4}$ K) deposited at 6.7 K and warmed up at a rate of 0.5 K per minute. The derived column densities are ${N}_{{\,\rm{CH}\,}_{4}}$ (CO _2 ) = $2.9{7}_{-0.57}^{+0.37}× 1{0}^{17}$ cm ^−2 and ${N}_{{\,\rm{CH}\,}_{4}}$ (H _2 O) = $1.0{2}_{-0.27}^{+0.46}× 1{0}^{17}$ cm ^−2 . According to the best fit, solid methane is mostly surrounded by CO _2 rather than H _2 O. The residual analysis reveals the unassigned region at 1283–1297 cm ^−1 (7.71–7.79 μ m), which is tentatively assigned to nitrous oxide (N _2 O) in various environments.